Comparative effectiveness of H7N9 vaccines in healthy individuals - Dan Zheng; Feixia Gao; Cheng Zhao; Yahong Ding; Yemin Cao; Tianhan Yang; Xuesong Xu; Ze Chen (Taylor & Francis Group, 2019)
Background: Avian H7N9 influenza viruses possess a potential pandemic threat to public health worldwide, and have caused severe infection and high mortality in humans. A series of clinical trials of H7N9 vaccines have been completed. Meta-analyses need to be performed to assess the immunogenicity and safety of H7N9 vaccines. Methods: Database research with defined selection criteria was conducted in PubMed, Cochrane Central Register of Controlled Trials, the World Health Organization's International Clinical Trials Registry Platform, ClinicalTrials.gov, etc. Data from randomized clinical trials regarding the immunogenicity and safety of H7N9 vaccines were collected and meta-analyzed. Results: For non-adjuvanted H7N9 vaccines, high dose formulations induced limited immunogenicity and increased the risk of local and systemic adverse events, simultaneously. For adjuvanted H7N9 vaccines, on the one hand, ISCOMATRIX, MF59, AS03 and aluminium adjuvants applied in H7N9 vaccines could improve immune responses effectively, and non-aluminium adjuvants had superior performance in saving vaccine dose; on the other hand, aluminium adjuvant had the advantages of safety amongst these adjuvants applied in H7N9 vaccines. Conclusion: H7N9 influenza vaccines with adjuvant might represent the optimal available option in an influenza pandemic, at present.